The influence of the dynamic change of fear: how gender-specific messages affect anti-smoking intentions - Gu, Rui (Nanyang Technological University, 2023)
The drive model, one of the earliest attempts to reveal the mechanisms and effects of fear appeals, inspires the idea that fear should rise and fall to successfully predict persuasion. This dynamic change of fear in its entirety is captured by an inverted-U trajectory. However, important questions regarding how the fear trajectory emerges, grows, and influences persuasion need to be addressed. Therefore, this study employed tailored fear appeals, the gender-specific graphic warning labels, to fill the conceptual gaps in the model. The findings showed that gender specificity as a message type and participants’ genders as an audience characteristic led to different changes of fear and, thus, varying levels of persuasion. First, not only was the female-matched fear curve sharper in shape, but it also predicted lower cigarette-purchase intentions than the female-mismatched curve. However, two different shapes of fear curves were not always sufficient to constitute a significant difference in persuasion: females receiving the matched GWLs showed a more peaked fear trajectory, but that sharper trajectory did not predict greater persuasion compared to when males receiving the male-specific GWLs. This study helps to clarify the potential boundaries and thresholds of the fear trajectories to produce persuasion. Consistent with the drive model, the results also indicate that recognition of the changing nature of fear is beneficial to craft maximally persuasive messages.